Superparamagnetic Nanocomposites Based on the Dispersion of Oleic Acid-Stabilized Magnetite Nanoparticles in a Diglycidylether of Bisphenol A-Based Epoxy Matrix: Magnetic Hyperthermia and Shape Memory - Puig, Julieta (2012)
Superparamagnetic nanocomposites were obtained by dispersion of oleic acid (OA)-coated magnetite NPs in an epoxy system based on diglycidylether of bisphenol A (DGEBA) modified with OA. Dispersion of conventional oleic acid stabilized magnetite NPs in a typical epoxy matrix is not possible due to the dissimilar chemical structures of the organic coating and the reactive solvent. However, by modification of a DGEBA-based epoxy with 20 wt% OA, we obtained a suitable reactive solvent to disperse up to at least 8 wt% of OA-stabilized magnetite NPs. A tertiary amine was used to catalyze the epoxy-acid reaction and initiate the homopolymerization of the epoxy excess. Both reactions occurred practically in series, first the epoxy-acid and then the epoxy homopolymerization. It was necessary to complete the first reaction to attain a very good dispersion of magnetite NPs in the reactive solvent previous to the occurrence of the final reaction. Magnetization curves and TEM images revealed a uniform dispersion of individual nanoparticles in the cross-linked epoxy. A sample containing 8 wt% OA-coated magnetite NPs exhibited a temperature increase of 25 °C at its surface when exposed to an alternating magnetic field. The temperature increase was enough to induce the shape memory effect of the nanocomposite.